Effects of Wall Temperature on the Viscoelastic Fluid Flow through Gradual Contraction - Ahmad Suhaimi Bin Sokiman, Ahmad Suhaimi (Universiti Teknologi Petronas, 2010)

(untitled)
This preliminary report will provide the readers about the preliminary research regarding “Effects of Wall Temperature on The Viscoelastic Fluid Flow through Gradual Contraction”.